METHODS OF USING GAMING TECHNOLOGIES IN TEACHING A FOREIGN LANGUAGE AT SCHOOL (Journal of Science-Innovative Research in Uzbekistan, 2025)
In recent years, the integration of gaming technologies into educational practices has gained significant traction, particularly in the realm of foreign language instruction. This article explores various methods and strategies for incorporating gaming elements into language teaching at schools. By leveraging the engaging and interactive nature of games, educators can enhance student motivation, facilitate immersive learning experiences, and improve language acquisition. We will discuss different types of games, their educational benefits, and practical examples of how they can be effectively implemented in the classroom.